The rise of multi-bi aid and the proliferation of trust funds - Vera Z. Eichenauer (Edward Elgar Publishing, 2015)
Since the end of the Cold War, development assistance has been transformed in various ways. The aid allocation and the aid effectiveness literature intensively discuss the qualitative reorientation from geopolitical towards actual poverty reduction objectives and the donors' related geographical and sector choices. The introduction of the Millennium Development Goals (MDGs), the World Bank's poverty reduction strategies (PRS), and the new principles for aid developed in the context of the Paris Declaration have all triggered important dynamics that also found a corresponding reflection in the literature. In parallel, there has been a much more silent revolution of funding mechanisms, widely discussed within aid agencies, but so far without any significant analysis in the academic literature. While donor countries traditionally face a binary choice between two channels for official development assistance (ODA), namely, the bilateral and the multilateral channel, they now increasingly opt for a combination of the two, generally called 'multi-bi' aid. In this context, they channel funds to an international development organization (IDO), a multilateral agency that implements development activities, but without providing the IDO with the authority to spend these funds at its own discretion. Owing to this earmarking to specific areas in which the funds may be used, multi-bi aid differs substantially from traditional core funding to multilaterals. A further difference consists in the voluntary nature of multi-bi contributions that provide much more flexibility to the donor government.